Winnipeg and Minneapolis Bank Resources Compared, 1876-1926 - Fay, Terence (Urban History Review / Revue d'histoire urbaine, 1985)
By 1926 Manitoba had a population one-third that of Minnesota, and yet the bank resources it accumulated to that year represented only one-tenth that of Minnesota banks. What can explain the much higher generation of banking resources in Minnesota and Minneapolis as compared with a much lower generation of resources in Manitoba and Winnipeg? A study of the number of branches in Manitoba and the level of cheque clearances in Winnipeg reveal that these branches were as vigorous as the number of unit banks and cheque clearances in Minnesota. However, by comparing the growth of Minneapolis industries with those in Winnipeg, it becomes apparent that Winnipeggers did not, as Minneapolis entrepreneurs did, develop the specialized manufacturing for export, the consequent company head offices, and the transportation services necessary to generate endogenous capital resources. Rather Winnipeg branches were the result of a banking system transported from Montreal and Toronto which, at the same time, it supplied financial resources for Manitobans, also served the goals of its Central Canadian directors and shareholders, and therefore, proceeded to integrate Winnipeg commercial resources into this central urban network. The Minneapolis industrial entrepreneurs, by contrast, established banks which generated their own financial resources and banking procedures. This meant that the Minneapolis bank owners were determined to shape the investment and growth of their metropolitan region. In Winnipeg, however, the branches served their Montreal and Toronto owners who were determined to encase Winnipeg businesses firmly within that Central Canadian urban system.